The Concept Development of Human Resource Management Based Gamification for Millennial Workforce - Indah rahayu; Fariha azzahra (LPPM Universitas An Nuur, 2022)
Background: Research on generational values in the three workforces shows a shift in dominant work values in the millennial workforce. An organization that will optimize the role of the millennial workforce needs to understand the characteristics of the nature of their work. In addition, organizations need to develop policy designs that are in accordance with the millennial employee workstyle, one of which is by using the concept of gamification. Purpose: The purpose of this study is to develop a concept related to HRM practices and policies with a gamification approach. Methods: The research method used is a literature survey to define concepts and develop measurements. Conclusion: The results of the study found that HRM-based Gamification can be defined as the implementation of HR practices by making these practices seem more fun, relaxed and informal. Suggestion: Further research will be conducted to validate the concept definition and measurement of HRM based gamification with quantitative methods. In addition, future research will also be conducted to examine the impact of gamification-based HRM on job satisfaction and engagement of the millennial workforce.